Forma Di Vita Di Francesco E Chiara: Invito Alla Libertà In Cristo : Dalla conversione alla contemplazione - Di Muro, Raffaele (Miscellanea francescana, 2022)
Francis and Clare, through "their" form of life, invite you to a path where dialogue with God and the signs coming from him have absolute prevalence and are favoured by the practice of an ascetic journey that has the purpose of achieving a continuous purification that makes you more receptive to the divine plan concerning yourself. The following of Christ is thus made possible and much facilitated so that the experience of each one has an exquisitely evangelical flavour.